Unveiling high-power and high-safety lithium-ion battery separator based on interlayer of ZIF-67/cellulose nanofiber with electrospun poly(vinyl alcohol)/melamine nonwoven membranes - Wu, Xiaowei; Karuppiah, Chelladurai; Wu, Yi–Shiuan; Zhang, Borong; Hsu, Lifan; Shih, Jengywan; James Li, Ying Jeng; Hung, Tai-Feng; Ramaraj, Sayee Kannan; Jose, Rajan; Yang, Chun Chen (Elsevier Ltd, 2024)
Due to the poor thermal stability of conventional separators, lithium-ion batteries require a suitable separator to maintain system safety for long-term cycling performance. It must have high porosity, superior electrolyte uptake ability, and good ion-conducting properties even at high temperatures. In this work, we demonstrate a novel composite membrane based on sandwiching of zeolitic imidazole frameworks-67 decorated cellulose acetate nanofibers (ZIF-67@CA) with electrospun poly(vinyl alcohol)/melamine (denoted as PVAM) nonwoven membranes. The as-prepared sandwich-type membranes are called PVAM/x%ZIF-67@CA/PVAM. The middle layer of composite membranes is primarily filled with different weight percentages of ZIF-67 nanoparticles (x = 5, 15, and 25 wt%), which both reduces the non-uniform porous structure of CA and increases its thermal stability. Therefore, our sandwich-type PVAM/x%ZIF-67@CA/PVAM membrane exhibits a higher thermal shrinkage effect at 200 °C than the commercial polyethylene (PE) separator. Due to its high electrolyte uptake (646.8%) and porosity (85.2%), PVAM/15%ZIF-67@CA/PVAM membrane achieved high ionic conductivity of 1.46 × 10-3 S cm−1 at 70 °C, as compared to the commercial PE separator (ca. 6.01 × 10-4 S cm−1 at 70 °C). Besides, the cell with PVAM/15%ZIF-67@CA/PVAM membrane shows an excellent discharge capacity of about 167.5 mAh g−1after 100 cycles at a 1C rate with a capacity retention of 90.3%. The ZIF-67 fillers in our sandwich-type composite membrane strongly attract anions (PF6-) through Lewis' acid-base interaction, allowing uniform Li+ ion transport and suppressing Li dendrites. As a result, we found that the PVAM/15%ZIF-67@CA/PVAM composite nonwoven membrane is applicable to high-power, high-safety lithium-ion battery systems that can be used in electric vehicles (EVs).